Forcibly retrieving bodies of deceased persons with confirmed COVID-19: A lesson learned from the COVID-19 pandemic - Singgih, Doddy S.; Koesbardiati, Toetik (Faculty of Social and Political Science, Universitas Airlangga, 2024)
During the pandemic in Indonesia, 43 cases of forced retrieval of COVID-19-confirmed bodies and attempts to bury them by their families were recorded in online media. In 2020, 31 cases occurred and in 2021, there were 12 cases until April. This study aims to describe the religious culture on bereavement of the community towards death due to COVID-19 where the community retrieves the bodies by force. This study used qualitative method. Data were collected from randomly selected online media. Interviews with hospital morticians were conducted to complement data on forced body retrieval and similar previous studies. The results show that religious and cultural values are the driving factors for forced body retrieval. On the other hand, factors such as stigma and misinformation are allegedly reinforcing the act of forced body retrieval. The lesson learned from this is to involve cultural and religious systems along with the implementation of health protocols when treating patients with confirmed COVID-19. However, this must be balanced with adequate information for the community.